Transforming Mathematics Learning to Increase Students' Confidence, Concept Understanding, and Problem Solving Ability - Lailatul Jannah; Syaharuddin; Abdillah (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
The gap between the ideal objectives of mathematics learning and classroom realities is reflected in students’ low self-efficacy, conceptual understanding, and problem-solving abilities. One contributing factor is the continued reliance on conventional instructional models. This study aims to examine the effect of the Discovery Learning model on students’ self-efficacy, conceptual understanding, and mathematical problem-solving skills. The research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design, involving 40 eighth-grade students divided into experimental and control groups. Data were collected using questionnaires and achievement tests, which were analyzed through linear regression, t-tests, and N-Gain analysis. The results indicate that the Discovery Learning model has a significant effect on all three variables, with N-Gain scores exceeding 80%, indicating a high level of improvement. The study concludes that Discovery Learning is effective in enhancing overall mathematics learning outcomes. The implications of this study suggest that Discovery Learning can be integrated as an active, student-centered instructional strategy to improve the quality of mathematics learning. Furthermore, the findings provide a valuable foundation for teachers and educational policymakers in designing learning environments that sustainably foster students’ cognitive competencies, affective development, and mathematical problem-solving skills.